2022
DOI: 10.1007/s11695-022-06197-4
|View full text |Cite
|
Sign up to set email alerts
|

A Literature Review of Taste Change and Zinc Deficiency After Bariatric Surgery: Could There Be a Causal Link?

Abstract: In this review, we collated evidence relating to taste change and zinc deficiency in relation to bariatric surgery (BS) and effects of zinc replacement on taste perception and speculate on the possible role of zinc deficiency to induce taste change after BS. A literature search was conducted (33 studies, N = 3264). We showed that taste change and zinc deficiency are frequent complications after BS, which both typically occurred at 6 months post-surgery. Our analysis did not support a causal link between the tw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 54 publications
1
4
0
1
Order By: Relevance
“…These results indicate that hypogeusia is a frequent side effect after both types of BS, but more frequent among MGB patients. These results are thus in agreement with our recent review which included a variety of patient populations studied in different clinical settings that found that taste change was reported more frequently among gastric bypass patients than among those undergoing other types of BS [ 10 ]. This study also used a taste strip test to compare the outcomes after both methods of surgery: these tests confirmed that hypogeusia was more frequent after MGB than after SG.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…These results indicate that hypogeusia is a frequent side effect after both types of BS, but more frequent among MGB patients. These results are thus in agreement with our recent review which included a variety of patient populations studied in different clinical settings that found that taste change was reported more frequently among gastric bypass patients than among those undergoing other types of BS [ 10 ]. This study also used a taste strip test to compare the outcomes after both methods of surgery: these tests confirmed that hypogeusia was more frequent after MGB than after SG.…”
Section: Discussionsupporting
confidence: 92%
“…No studies using patient self-reports contradict this idea of taste change following BS, though controversy has arisen based on variance in detecting taste changes using quantitative or experimental methods such as taste detection and (10). In contrast to previous experimental studies that did not detect 3 (13.6) 0 (0) -0 (0) 0 (0) - † Te test for a diference was performed by using an independent t-test for parametric variables.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For ease of presentation, we have compiled the literature that has been included in this analysis into Table 1. 10 Saudi Arabia Literature Review…”
Section: Quality Assessment and Data Synthesismentioning
confidence: 99%
“…The study found that supplementing with 45-50 mg of zinc sulfate, a higher dosage than the current recommendation, was successful in enhancing taste. 10 According to Dagan et al's research, experts recommend specific nutritional care during the perioperative and long-term postoperative periods. This includes taking two doses of multivitamin-mineral supplements containing iron, folic acid, zinc, copper, selenium, and thiamin (equivalent to 200% of the recommended daily allowance), a 600-mg calcium supplement daily, and 3000 IU of vitamin D per day (either ergocalciferol or cholecalciferol).…”
Section: Dagan Et Almentioning
confidence: 99%